2011
DOI: 10.4049/jimmunol.1003756
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Signaling Promotes Fibrosis In Vitro in a Bronchopulmonary Dysplasia Model by Activating the Extrinsic Coagulation Cascade

Abstract: Neonatal respiratory distress syndrome can progress to bronchopulmonary dysplasia (BPD), a serious pulmonary fibrotic disorder. Given the involvement of the extrinsic coagulation cascade in animal models of lung fibrosis, we examined its role in BPD. We observed a higher number of neutrophils expressing tissue factor (TF) in bronchoalveolar lavage fluid (BALF) from infants with BPD than from those with uncomplicated respiratory distress syndrome together with a parallel decrease in TF and connective tissue gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 43 publications
(47 reference statements)
2
34
0
10
Order By: Relevance
“…We examined in vitro the effect of phospholipids on the collagen production and proliferation/migration of myofibroblasts. We have previously demonstrated that TGFb1 can increase both collagen production and myofibroblast migration [22,41]. In this study, treatment of myofibroblasts with various concentrations of phospholipids resulted in a statistical significant reduction of both basal and TGFb1-induced collagen production.…”
Section: Discussionmentioning
confidence: 72%
“…We examined in vitro the effect of phospholipids on the collagen production and proliferation/migration of myofibroblasts. We have previously demonstrated that TGFb1 can increase both collagen production and myofibroblast migration [22,41]. In this study, treatment of myofibroblasts with various concentrations of phospholipids resulted in a statistical significant reduction of both basal and TGFb1-induced collagen production.…”
Section: Discussionmentioning
confidence: 72%
“…This is not surprising, since ET-1 signaling has been shown to be involved in the disruption of molecular pathways that promote alveolar development and repair, especially in the immature lung [6,10]. Given our reported time-specific differences in plasma CT-proET-1 levels between neonates who did or did not develop BPD, we propose that CT-proET-1 measurements at the end of the first week of life might be of maximum diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In preterm newborns, raised plasma ET-1 levels have been related to the development of respiratory distress syndrome [3] whereas an early increase of ET-1 in the tracheal aspirate has been shown to correlate with subsequent progression to BPD [4]. In addition, the antiangiogenic effect of ET-1 has been linked to the pathogenesis of BPD [5] and evidence from human ex vivo models suggests that ET-1 signaling may play a critical role in the development of a BPD-like fibrotic process in the immature lung [6]. Although ET-1 is unstable in the peripheral blood and therefore less suited for diagnostic use, the more stable C-terminal fragment of the ET-1 precursor (CT-proET-1) can be used to estimate ET-1 release [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the potential role of CTGF in BPD development and progression. The clinical association of CTGF with BPD is best established by studies demonstrating increased CTGF concentrations in bronchoalveolar lavage fluid from preterm infants developing BPD (5) and increased CTGF expression in lung tissues of infants who died of BPD (6). Multiple studies have examined the potential role of CTGF in experimental BPD and demonstrated that increased CTGF expression is associated with chronic hyperoxia as well as mechanical ventilationinduced lung injury in neonatal rodents (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%